2022-RA-1678-ESGO Treatment patterns and outcomes for older women with ovarian cancer in ireland. (20th October 2022) - Moloney, Carolyn; Lynch, Paula; Kieran, Ruth; Holmes, Orla; Korpanty, Greg; Stratton, John; McCaffrey, John; Duffy, Austin; Calvert, Paula; Hassan, Anees; Kalachand, Roshni
Abstract : Introduction/Background: The treatment of older women with ovarian cancer is challenging due to increased pre-existing co-morbidities and frailty, often leading to less radical treatment than the standard of care. Older women are frequently excluded from clinical trials. Recent studies such as the EWOC-1 study focused on elderly women with ovarian cancer suggest worse outcomes associated with less radical treatment approaches. Methodology: Women diagnosed with ovarian cancer ≥65 years old referred to oncology services at three Irish University Hospitals between 2015 and 2021 were included. We evaluated patterns regarding surgery and chemotherapy sequencing, choice of agent and completion rates, according to age group. Survival outcomes were examined by Kaplan Meier analysis. The study received ethical approval. Results: 190 patients were included in this study. 65.26% (124) of these women had an ECOG performance status of 0–1 at diagnosis. 129 patients (67.89%) had (FIGO) stage III or stage IV disease at diagnosis. 55% of all stage III/IV patients had optimal debulking surgery. 37% of stage III/IV patients received neoadjuvant chemotherapy followed by surgery and 27% had surgery followed by chemotherapy. Women in the ≥75 group were more likely to receive single agent carboplatin (38%), compared to women aged 65–74 years (30%). Median overall survival for all stage III/IV patients who received SA Carboplatin was 15 months versus 22 months for Carboplatin and Paclitaxel groups. BRCA testing was sub-optimal in this age group at 28% of all patients although routine BRCA testing has only been available in Ireland since 2019. Conclusion: Elderly ovarian cancer patients, particularly those ≥75 years, may receive less radical treatment approaches than standard of care. Our cohort suggests improved survival with carboplatin/paclitaxel, although our cohort is too small to draw significant conclusions. Rates of BRCA testing were low. Geriatric oncology assessments should be incorporated into treatment decisions.